National Innovation Capability Variables and Dimensions - Ahmad Dading Gunadi; Yandra Arkeman; Rizal Syarief Siaiful Nazli; Teguh Rahardjo; Aulijati Wachjudiningsih (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
The purpose of this paper is to analyze the dimensions and variables of National Innovation Capability. The findings in this paper are to refine the National Innovation Capabilities Dimension model developed by Chang and Lin (2012) by integrating a Network Dimension of Innovation. This paper analyzes the dimensions and variables of National Innovation Capability through a system approach that includes Input Sub System, Process Sub System, and Output Sub System. Network Dimensions Innovation is an integral part of the National Innovation Capabilities Dimension. This dimension is an important part, because the National Innovation Capability will largely depend on how innovative actors form networks and interact among them. The dimensions of National Innovation Capability are integrated into three sub system in a systems approach that includes input, process, and output. In the input consists of Dimensions of Innovation Resources. In the process consists of Innovation Demand Dimension, Innovation Network Dimension and Innovation Diffusion Dimension. In the output consists of Dimensions of Innovation Output. Each Dimension has some different variables. The entire dimensions and variables of these three sub system become unified as a Dimension and Variable of National Innovation Capability. Keywords: National Innovation Capability, Dimensions, Variables, Sub Systems